Effect of different mouth washes on dental biofilm from orthodontic elastic and wire ligature / Dr. Saba F. Hussain ... [et al.] - Hussain, Saba F.; Al-Bayaty, F.H.; Abdul Rahim, N.R.; Abdulla, Mahmood M.; Said Gulam Khan, Hasnah (2010)
Appliance that temporarily cemented or bonded on the patient teeth which can’t be removed by patient (Daljit, 2008).